A responsabilidade civil do síndico - Karpat, Rodrigo (2022)
The figure of the manager in the condominium takes on ever-greater proportions, which has occurred since Law 4.591/64, this is due to the natural development of society added to the population increase, growth in the number of condominiums, and what made the need for professionalization vehement the management of condominiums and, as a consequence, the need for a “specialist” manager to manage the projects, hence the need for professionalization of the profession. Building condominiums are the way found by developers for their projects and thus meet the deficient demand for housing. With this growth, the civil responsibilities of the liquidator increase and take on proportions in which it is even discussed, whether the manager's responsibility would be objective or specific, and also, what are the limits between the liquidator's responsibility in the exercise of his functions, and the responsibility condominium, as well as in which cases the manager can be held personally liable. The trustee's civil liability occurs when the duties of the position are not fulfilled, causing damages to the unit owners or third parties. What can happen by omission or by an action, going beyond contractual or extra-contractual limits, in a consumer relationship in the case of the professional liquidator or in a civil relationship, with abuse of rights or for an unlawful act. The trustee has an essential role in the management of the condominium, not only for being the legal representative, but also for exercising the executive functions of the administrator. These and other free limits in this dissertation so that it is possible to understand the limits of civil liability of the liquidator